P671 Effect of genetic polymorphisms in the folate pathway on the efficacy and safety of methotrexate in Crohn's disease. (27th May 2021) - Salazar, J; Gordillo Abalos, J; Fernández, A; Esteve, M; Pérez Gisbert, J; Busquets, D; Lucendo, A; Márquez, L; Guardiola, J; Martin, M D; Iglesias, E; Monfort, D; et al.
Abstract: Background: Methotrexate (MTX) is currently used in steroid-dependent patients with moderate-to-severe Crohn's disease (CD) when thiopurines have failed or are contraindicated. Although its efficacy has been proved for both induction and maintenance of remission, its use is limited due to the rate of associated adverse events. Polymorphisms in the folate pathway might predict the efficacy and toxicity of MTX. Our aims were to evaluate the predictive value of these polymorphisms of MTX efficacy and safety in CD. Methods: Patients from ENEIDA registry of GETECCU who were treated with MTX on monotherapy and of whom genomic DNA was available, were identified. Clinical efficacy and MTX-related toxicity were collected, and 10 variants from ATIC, DHFR, MTHFR, RFC1, ABCB1 and ABCC3 genes were genotyped with TaqMan assays. Results: One hundred and twenty nine patients were included, 55% were female and 31% active smokers. MTX was used as first and second-line therapy in 10% and 60% of patients, respectively, at a mean dose of 22 mg and for a median time of 14 months. Thirty-seven per cent of patients achieved clinical remission, whereas 34% were non-responders (MTX failure). Forty patients (30%) developed MTX-related toxicity, with nausea and vomiting, myelotoxicity and hepatotoxicity as the most frequent adverse events (37%, 15% and 15%, respectively). MTX was discontineud in 19% of the patients due to toxicity. In the multivariable analysis, patients with the AA genotype for the rs408626 DHFR variant was predictive of a higher efficacy as compared to the G allele carriers (RR 0.372, p=0.026), and smoking was associated with a higher risk of MTX therapy failure (RR 2.676, p=0.015). Moreover, the CC genotype for the rs1476413 MTHFR variant and the TT genotype for the rs4793665 ABCC3 variant were independently associated with a higher risk of MTX toxicity (RR 2.357, p=0.038 and RR 2.368, p=0.044, respectively). Conclusion: Genetic polymorphisms related to the folate pathway (mainly the variant rs408626 of DHFR, rs1476413 of MTHFR and rs4793665 of ABCC3 ) seem to impact on MTX efficacy and toxicity in CD. Smoking could also influence MTX efficacy.